HER-3 expression in HER-2-amplified breast carcinoma - Czopek, Jacek; Pawlęga, Janusz; Fijorek, Kamil; Püsküllüoğlu, Mirosława; Różanowski, Paweł; Okoń, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study : To determine whether the expression of HER-3 influences the survival of HER-2 positive patients with breast cancer (BC). Material and methods : In the present work, the expression of HER-3 in a group of 35 HER-2 positive patients with BC was studied by performing immunohistochemistry (IHC) in formalin-fixed paraffin embedded tissues. Results : Higher HER-3 status if estimated by IHC correlated significantly with older age of the patients. HER-3 expression did not correlate with estrogen or progesterone receptor status, pT or pN. There was also no significant difference in disease-free or overall survival (DFS and OS) between groups with different HER-3 expression, although some tendencies were seen as HER-3 expression in over 50% of cells was a factor of worse 5- and 10-year survival. Conclusions : Further studies should be performed on a larger group of patients to confirm the prognostic role of HER-3 status determined by IHC in BC.